Pengaruh Electronic Service Quality, Electronic Trust dan Financial Well-Being terhadap Repurchase Intention Produk Oclo Official pada Marketplace Shopee di Kota Bandung - Winarni; Dedy Anshari Harahap (UNISBA Press, 2023)
Abstract. Current technological developments have changed consumer behavior in shopping for needs, one of which is changing the way shopping for fashion needs becomes easier and more practical with the presence of various online shopping sites (Marketplace) that present several online fashion stores on Marketplace so that it can make it easier for consumers to make purchases. by online. This study aims to find out how the description and influence of Electronic Service Quality, Electronic Trust, Financial Well-being and Repurchase Intention on Oclo Official on the Shopee Marketplace.This research is included in the type of descriptive research with quantitative methods. The sampling technique used is nonprobability sampling, namely purposive sampling. The population in this study were consumers who had purchased Oclo Official products at least 1-2 times, and obtained a sample of 215 people. Furthermore, the data analysis used is descriptive and statistical analysis, namely by using multiple linear regression analysis, F test and T test, and the coefficient of determination.The results of this study indicate that Electronic Service Quality has a positive and significant effect on Repurchase Intention, Electronic Trust has a positive and significant effect on Repurchase Intention, and Financial Well-being has a positive and significant effect on Repurchase Intention. Then simultaneously the influence of Electronic Service Quality, Electronic Trust, Financial Well-being has a positive and significant effect on Repurchase Intention. Abstrak. Perkembangan teknologi saat ini telah mengubah perilaku konsumen dalam berbelanja kebutuhan, salah satunya yaitu mengubah cara berbelanja kebutuhan fashion menjadi lebih mudah dan praktis dengan hadirnya berbagai macam situs belanja online (Marketplace) yang menghadirkan beberapa toko fashion online di Marketplace sehingga dapat memudahkan konsumen dalam melakukan pembelian secara online. Penelitian ini bertujuan untuk mengetahui bagaimana gambaran serta pengaruh Electronic Service Quality, Electronic Trust, Financial Well-Being dan Repurchase Intention di Oclo.Official pada Marketplace Shopee. Penelitian ini termasuk ke dalam jenis penelitian deskriptif dengan metode kuantitatif. Teknik sampling yang digunakan adalah non probability sampling yaitu purposive sampling. Populasi pada penelitian ini adalah konsumen yang pernah melakukan pembelian produk Oclo.Official minimal sebanyak 1-2 kali, dan didapatkan sampel sebesar 215 orang. Selanjutnya analisis data yang digunakan adalah analisis deksriptif dan statistik yaitu dengan menggunakan analisis regresi linier berganda, uji F dan uji T, dan koefisien determinasi. Hasil dari penelitian ini menunjukan bahwa Electronic Service Quality berpenguruh positif dan signifikan terhadap Repurchase Intention, Electronic Trust berpengaruh positif dan signifikan terhadap Repurchase Intention, dan Financial Well-Being